Уравнение абсорбции паров низкомолекулярных веществ их растворами - Романкевич, О.В. (Видавничий дім "Академперіодика" НАН України, 2007)
We obtain the equation for the polymolecular absorption isotherm under the sorbate solubility in a sorbent with the assumption that the solvate is forming. An application of this equation, which coincides with the BET equation by form, for describing the vapor sorbtion by the solutions of low-molecular substances in the case of the formation of solvates is shown.